Synthetic seismic modelling - an application to interpretation of structurally complex areas - Frankowicz, E.; McClay, K.; Pietsch, K. (TRABAJOS DE GEOLOGÍA, 2009)
This study presents the application of synthetic seismic modelling to structural interpretation of a complex zone of interaction between faults forming a conjugate system in the northern part of the Bonaparte basin, Australia. Three velocity models of this poorly imaged zone, assuming hard, semi-hard and soft linkage between faults were introduced. For each model the theoretical wavefield was then calculated and compared with the real seismic registration. This comparison allowed for the conclusion that the soft linkage is the most likely type of interaction with in the conjugate fault systemin this area.